ANALISIS WACANA BERITA PEMERKOSAAN PADA SURAT KABAR INDOPOS - Nugroho, Yosia Kurnia (WACANA, Jurnal Ilmiah Ilmu Komunikasi, 2012)
At the presentation of news rape of women or women in the mass media will not be beneficial for the women as victims of rape. This is because the perpetrators of rape to be placed as the subject of the news, the news flow may also be held by the perpetrators, although the victim as the source of news stories for writers.